2017
DOI: 10.15835/nbha45110627
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Night-time Temperatures on Physiological and Biochemical Traits in Rice

Abstract: High nighttime temperatures impair rice yield. Additionally, heat stress periods have increased during the last years in the rice areas of the tropics. The aim of this study was to physiologically characterize six genotypes of rice (a commercial cultivar (ʻF60ʼ) and five selected lines (ʻIR 1561ʼ, ʻFLO 2764ʼ, ʻLV447-1ʼ, ʻCT19021ʼ, and ʻLV1401ʼ) subjected to two nighttime temperatures (24 and 30 °C), based on different physiological traits. When the collar formed on leaf 6 of the main stem, one group of six pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Reduced F V /F M indicates damage to PSII proteins, such as D1, or impairments of the repair system of PSII proteins (Gururani, Venkatesh, & Tran, 2015; Song, Yue, Zhao, & Hou, 2013). Reductions in F V /F M , due to HNT, align with previous studies of HNT and rice (Alvarado‐Sanabria, Garcés‐Varón, & Restrepo‐Díaz, 2017a, 2017b). In this study, we observed that even short periods of HNT (5.5 h of pre‐ or post‐midnight stress) can reduce F V /F M .…”
Section: Discussionsupporting
confidence: 88%
“…Reduced F V /F M indicates damage to PSII proteins, such as D1, or impairments of the repair system of PSII proteins (Gururani, Venkatesh, & Tran, 2015; Song, Yue, Zhao, & Hou, 2013). Reductions in F V /F M , due to HNT, align with previous studies of HNT and rice (Alvarado‐Sanabria, Garcés‐Varón, & Restrepo‐Díaz, 2017a, 2017b). In this study, we observed that even short periods of HNT (5.5 h of pre‐ or post‐midnight stress) can reduce F V /F M .…”
Section: Discussionsupporting
confidence: 88%
“…When NT increases, the excessive consumption of carbohydrates results in biomass decrease in corn (Hoeft et al, 2000). The increase in respiration rate also occurred in soybean and rice under HNT (Alvarado-Sanabria et al, 2017;Djanaguiraman et al, 2013;Mohammed & Tarpley, 2009). Although the results showed a negative correlation between respiration rate and HNT, its association with crop growth, yield components and physiological response in soybean under HNT has not been fully evidenced.…”
Section: Introductionmentioning
confidence: 80%
“…HNT tended to decrease yield (Figure 2(c)). The yield decline under HNT has been observed in chamber and field-level studies for rice (Alvarado-Sanabria et al, 2017;Mohammed & Tarpley, 2009Peng et al, 2004;Y. Zhang et al, 2013) and in a phytotron study of the combination of high daytime and night temperatures for soybean growth (Gibson & Mullen, 1996).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For this reason, in the SD of August, the highest yield and the LCB reached 25 μmol CO 2 / μmol CO 2 respiration; this, however, is explained by the lower nighttime temperature that occurred in this SD. The above is favorable for rice plants since this environmental condition decreases their respiration rate (Alvarado et al, 2017). Furthermore, this condition affects the availability of carbohydrates for grain filling, so the magnitude of respiration can increase or reduce yield (Peraudeau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%